Numerical Study of Magnetohydrodynamic Flow of Dusty Fluid Through Different Channels - Lal, Madan; Agarwal, Swati; Kumar, Yogendra (Communications in Mathematics and Applications, 2021)
In this paper, Magnetohydrodynamic (MHD) flow through various channels such as rectangular, hexagonal, octagonal, decagonal, dodecagonal, and tetradecagonal channels of dusty gas and dust particles has been analyzed under the influence of magnetic field parameters and time. Numerical values of the velocity of dust particles and gas were calculated using Laplace transform for a non-dimensional equation. It is observed that for a given value of the magnetic parameter, the velocity of gas and dust particles decreases increases alternately as we move from one channel to another channel and found that for a particular channel, the velocity of gas and dust particles decreases as the value of magnetic field parameter increases. It is also observed that for a given value of the magnetic parameter, the velocity of gas and the velocity of dust particles increase with time. The velocity of dust particles is less than the velocity of the gas.
Keywords: Channel; Magnetic parameter; Laplace transform; Dusty gas; Dust particles